DEVELOPMENT OF A SYSTEM FOR MODELING THE PROCESS OF PETROLEUM PRODUCTS PROCESSING BASED ON FUZZY LOGIC - Mamasadikov Yusupjan; Mamasodikova Nodira Yusubjonovna; Alixonov Elmurod Jamoldinovich (International Journal of Innovations in Engineering Research and Technology, 2023)
Methodological aspects of intellectual system (IS) formation and their usage for forecasting of petro-chemical processes connected with physical-chemical and technology of industrial processes are considered. The principles of IS creation on the base of generalization of industrial units operation experience for special data processing in computer regime for users are expounded. Methods of forming of physical-chemical models of heterogeneous catalytic processes counting catalyst deactivation are generalized. A computer modeling system refining processes using a systematic approach strategy. At the heart of each system is non-stationary mathematical model of a catalytic process. A production-frame model to determine the causes of accidents in the machines included in the technological installation scheme. The model describes the user personnel actions on elimination emergency situation. Adaptation of industrial facility on a real software product through the development of communication module with a single thematic showcase of plant data.